2012
DOI: 10.4236/ojst.2012.22022
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary bone grafting with or without premaxilla osteotomy in adult alveolar clefts—Techniques and early outcome

Abstract: The outcome of alveolar bone grafting in adult patients is sparsely reported. Here, we present a description of the surgical techniques used in a Nigerian teaching hospital and a preliminary report of the first five cases of adult alveolar cleft bone grafting accomplished with or without repositioning the premaxilla. Although, evidence of bone resorption was observed within 6 months after the operation, satisfactory bone level and aesthetic outcome was recorded in all cases. We concluded that tertiary alveolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The reasons for this result may related to many factors such as: rapid bone resorption due to absence of functional stress on the bone, poor oral hygiene and width of the cleft. 16 The other factor could be the changes in the healing potential with increasing age. 17 These results come in agreement with the findings of study done by Dantana et al 18 , when they found that mean percentage of bone resorption after 3 months of alveolar cleft repair with the cancellous bone and marrow from the anterior iliac crest was 36.46%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for this result may related to many factors such as: rapid bone resorption due to absence of functional stress on the bone, poor oral hygiene and width of the cleft. 16 The other factor could be the changes in the healing potential with increasing age. 17 These results come in agreement with the findings of study done by Dantana et al 18 , when they found that mean percentage of bone resorption after 3 months of alveolar cleft repair with the cancellous bone and marrow from the anterior iliac crest was 36.46%.…”
Section: Discussionmentioning
confidence: 99%
“…The major causes for this results may be attributed to the patients themselves and surgical technique not to the graft material, such as poor oral hygiene, the tension of wound closure and extraction of teeth within the cleft site intra-operatively. 16…”
Section: Discussionmentioning
confidence: 99%